Changes in drought characteristics over China during 1961–2019 - Wen, Qixin; Chen, Huopo (Frontiers in Earth Science, 2023)
Drought is extremely complex and can be influenced by various factors. This study uses Penman-Monteith (PM) method to calculate the potential evapotranspiration and get the monthly drought metric of Standardized Precipitation-Evapotranspiration Index (SPEI) across China during the period of 1961-2019. Results show that the regions of the west of Northwest China (WNWC), Northeast China (NEC), and South China (SC) are reported to experience a wetting trend, while the droughts in the regions of the east of Northwest China (ENWC), North China (NC), and Southwest China (SWC) deteriorated over the past decades. Seasonally, the significant wetting trends mainly occurred in summer, autumn, and winter for WNWC, while mainly in winter for the region of NEC. Additionally, the droughts in China show an obvious interdecadal variability, with more severe droughts for the periods of 1961-1979 and 2000-2019, but with relatively fewer events in the period of 1980-1999. During the 1960s and 1970s, droughts in China are observed to mainly happen in summer and winter, while the droughts mainly occurred in autumn and winter during the 1980s and 1990s. Since the early 21st century, both the frequency and intensity of spring droughts have increased obviously and played a dominant role in seasonal droughts. Further studies indicate that the drought changes in southern China are mainly affected by the precipitation anomalies, while that in northern China are mainly influenced by the temperature and wind speed anomalies.